2023
DOI: 10.1021/acs.jpcc.3c00056
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical Synthesis and Fluoride Ion Conductivity Studies in SrSnF4 Polymorphs

Abstract: Investigations on SnF2-based solid electrolytes are gaining significant scientific attention because of their promising applications as solid electrolytes for all-solid-state fluoride ion batteries (FIBs) operating at room temperature. FIBs are potential alternatives for expensive Li-ion batteries with toxic and flammable liquid electrolytes. SrSnF4 belongs to the MSnF4 (M: Pb, Ba, and Sr)-type materials exhibiting a layered structure. Here, we present the structural and transport characteristics of two polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…PbSnF 4 is the best superionic conductor, exhibiting fluoride ion conduction, while BaSnF 4 is the most commonly used solid electrolyte known for RT FIB applications. 15,16,[19][20][21] Unlike MSnF 4 materials, only a few reports are available on MSn 2 F 5 (M: Na, K, Rb, Cs, NH 4 , Cs) materials. [22][23][24] Recently, Yu et al reported the application of KSn 2 F 5 solid electrolyte in a FIB, exhibiting a specific capacity of 150 mA h g −1 for more than 70 cycles.…”
Section: Introductionmentioning
confidence: 99%
“…PbSnF 4 is the best superionic conductor, exhibiting fluoride ion conduction, while BaSnF 4 is the most commonly used solid electrolyte known for RT FIB applications. 15,16,[19][20][21] Unlike MSnF 4 materials, only a few reports are available on MSn 2 F 5 (M: Na, K, Rb, Cs, NH 4 , Cs) materials. [22][23][24] Recently, Yu et al reported the application of KSn 2 F 5 solid electrolyte in a FIB, exhibiting a specific capacity of 150 mA h g −1 for more than 70 cycles.…”
Section: Introductionmentioning
confidence: 99%